Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.diabres.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

High burden of prediabetes and diabetes in three large cities in South Asia: The Center for cArdio-metabolic Risk Reduction in South Asia (CARRS) Study

Abstract: Aim To estimate the prevalence of, and assess factors associated with, diabetes and prediabetes in three South Asian cities. Methods Using a multi-stage cluster random sample representative of each city, 16,288 subjects aged ≥20 years (Chennai: 6906, Delhi: 5365 and Karachi: 4017) were recruited to the Centre for cArdiometabolic Risk Reduction in South-Asia (CARRS) Study. Fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA1c) were measured in 13720 subjects. Prediabetes was defined as FPG 100-125mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 26 publications
6
56
1
1
Order By: Relevance
“…Our study shows that the prevalence of diabetes in 2016 is 21.9% in the city of Chennai. The estimate was similar to that reported by the Center for cArdio-metabolic Risk Reduction in South Asia (CARRS) Study (26) in 2015, which was 22.8%. In that study, diagnosis of diabetes was made using the FPG and/or HbA 1c values.…”
Section: Discussionsupporting
confidence: 87%
“…Our study shows that the prevalence of diabetes in 2016 is 21.9% in the city of Chennai. The estimate was similar to that reported by the Center for cArdio-metabolic Risk Reduction in South Asia (CARRS) Study (26) in 2015, which was 22.8%. In that study, diagnosis of diabetes was made using the FPG and/or HbA 1c values.…”
Section: Discussionsupporting
confidence: 87%
“…Detailed baseline characteristics of the CARRS cohort are published elsewhere. [21][22][23][24] Briefly, the mean age was 42.4 (±13.3), 52.4% were female, 61% completed secondary schooling and the majority of respondents (72.5%) reported household income level <10 000 Indian rupees (US$200). Two-thirds (66%) of the study population had BMI ≥25, one-fifth (20%) of the respondents reported current tobacco use, and 37.5% had self-reported chronic conditions (hypertension, diabetes, heart disease, stroke or chronic kidney disease).…”
Section: Study Resultsmentioning
confidence: 99%
“…The proportion of diabetes to prediabetes was approximately 1:2 (i.e., one-third of total dysglycemia) in Chennai (22.8%:37.9% = 0.61), Karachi (16.3%:31.1% = 0.52), and Delhi (25.2%:47.6% = 0.54). [7]…”
Section: Prediabetes and Diabetesmentioning
confidence: 99%